Predictive value of CEA for survival in stage I rectal cancer: a population-based propensity score-matched analysis - Tarantino, Ignazio; Warschkow, René; Schmied, Bruno; Guller, Ulrich; Mieth, Markus; Cerny, Thomas; Büchler, Markus W.; Ulrich, Alexis (Journal of gastrointestinal surgery, 2016)
The aim of the study was to assess whether preoperative carcinoembryonic antigen (CEA) level is an independent predictor of overall- and cancer-specific survival in stage I rectal cancer.
Gesehen am 20.05.2020